Doctoral training strategy at the Cienfuegos University of Medical Sciences: experiences and results five years after its implementation - Miriam Iglesias León; Norma Mur Villar; José Aurelio Quiñones Díaz; Anays Núñez Herrera (Medisur)
The health professionals' permanent or continuous training and improvement process, requires that medical sciences cuban universities search for creative alternatives to train their professionals as science doctors. In response to this requirement, the Cienfuegos University of Medical Sciences, since 2017, developed a doctoral training strategy to validate the health professionals' training at all levels and thus contribute to the doctors in sciences training for the Cienfuegos provincial health system. This strategy has been perfected with the experiences obtained in its development up to the present. In this article the authors reflect on the results obtained in the doctoral training strategy of the Cienfuegos University of Medical Sciences based on the requirements of the Cuba's Scientific Degrees National Commission at present and the Higher Education and the Public Health System guidelines of the authorized centers, with which there are scientific collaboration agreements for this purpose.